BIGD Reflections 2021 - Brac Institute of Governance and Development (Brac University, 2022)
2021 was a year of profound significance for us as a nation, when we celebrated 50 years of Bangladesh. But celebration often provokes reflection. Our Golden Jubilee amidst the most consequential pandemic of the last 100 years and the climate that is changing faster than ever, compel us to critically reflect on our achievements, vulnerabilities and ways forward. For the BRAC Institute of Governance and Development (BIGD), it is a moment to reflect on our relevance to the future of Bangladesh.